FORECASTING SHALLOW LANDSLIDES USING PRECIPITATION DATA WITH THE HSB MODEL (2017)
The present study addresses a problem of slope stability by using a physically based model with the Hillslope- Storage Boussinesq (HSB) partial differential equation. This is used to evaluate shallow landslides, taking information from geotechnical parameters, slope profile, and rainfall. In this work, the equation was solved using finite difference methods in Python, by applying it to a theoretical area and calculating the safety factor. Five continuous periods of rainfall were considered in such equation. This data was taken from the records of the Automatic Weather Station in Manizales, Colombia. As a result, a monitoring of the stability slope through the safety factor was obtained, which was influenced in periods of 30 minutes, allowing a supervision of the surface soils landslide hazard by rainfall factor.